2018
DOI: 10.1186/s12864-018-4967-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of the interaction between Actinidia chinensis var. chinensis and Pseudomonas syringae pv. actinidiae in absence and presence of acibenzolar-S-methyl

Abstract: BackgroundSince 2007, bacterial canker caused by Pseudomonas syringae pv. actinidiae (Psa) has become a pandemic disease leading to important economic losses in every country where kiwifruit is widely cultivated. Options for controlling this disease are very limited and rely primarily on the use of bactericidal compounds, such as copper, and resistance inducers. Among the latter, the most widely studied is acibenzolar-S-methyl. To elucidate the early molecular reaction of kiwifruit plants (Actinidia chinensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 154 publications
4
40
0
Order By: Relevance
“…Infection occurs primarily via stomata (Fig. 3) [10,48,80]. For the onset of the infection, leaf wetness is necessary.…”
Section: Disease Cyclementioning
confidence: 99%
“…Infection occurs primarily via stomata (Fig. 3) [10,48,80]. For the onset of the infection, leaf wetness is necessary.…”
Section: Disease Cyclementioning
confidence: 99%
“…deliciosa , such as ‘Hayward’ ( Balestra et al., 2009 ). In addition, A. arguta , A. macrosperma , A. polygama and A. rufa were classified as tolerant to Psa ( Nardozza et al., 2015 ; Kisaki et al., 2018 ; Michelotti et al., 2018 ), but the molecular and biochemical mechanisms responsible for this tolerance are not fully known ( Wang et al., 2018 ; Nunes da Silva et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In A. chinensis , the genome assembly has demonstrated that more genes are associated with PTI, than with R gene based Effector-Triggered Immunity (ETI), implying a strong selective pressure on the expansion of genes involved in PTI 32 . Further evidence for this notion comes from studies exploring the transcriptome of the kiwifruit-Psa interaction the in period directly following inoculation 6365 . Data obtained from our study have provided a list of classes of gene families underlying the QTLs that might be directly or indirectly involved in the innate immune response of Actinidia and its host-pathogen relationship with Psa over the longer term in the field.…”
Section: Discussionmentioning
confidence: 99%